YIELD CAPACITY AND CHEMICAL COMPOSITION OF GREEN BEANS IN CULTIVARS OF KIDNEY BEAN BRED AT OMSK AGRARIAN UNIVERSITY IN THE SOUTH FOREST-STEPPE OF WESTERN SIBERIA - N. G. Kazydub; T. V. Marakaeva; О. A. Kotsyubinskaya (Овощи России, 2017)
In  2014-2016  the  assessment of  kidney bean  cultivars bred at Omsk State Agrarian University on yield capacity, quality, and biochemical  chemical compounds  in green beans, such as proteins, zinc, iodine, iron and sucrose was carried  out  in  the  south  forest-steppe  of  Western Siberia. The technological  parameters of  green  beans: the  shape  of  cross-section  area; pulpiness,  fibrous  or non-fibrous,  and bean thickness were estimated. Threeyear study showed that all tested cultivars bred at Omsk State  Agrarian  University  surpassed  control  cultivar  in yield capacity,  chemical composition  and technological parameters of green beans. The cultivar ‘Pamiyaty Rizhovoy’ gave a highest yield: 563.4 g/m2  in 2014; 622.8 g/m2 in 2015; and 620.4 g/m2  in 2016. It is worth noticing that this cultivar is also distinguished by contents of micro and macroelements: 21.20-28.68  mg/kg  of zinc; 0.012-0.018 mg/kg of iodine; and 1.8-3.2 mg/kg of iron. In the course of the study, it was noticed the dependence of  yield  capacity  on  hydrothermal  coefficient  (HC). In 2014-2015 the yield capacity was a lowest when the moisturization was insufficient at 0.7 HC. With increase of HC the yield was higher. With sufficient moisturization at 1.0 HC the highest yield of green beans was observed in 2016.  The estimation  of  kidney  bean  cultivars  bred  at Omsk State  Agrarian University showed  that  all beans were  distinguished  by  high  quality  parameters  in  the phase  of  technical  maturity,  such  as  pulpiness,  nonfibrous, thickness 0.5 to  1.0 cm, and green and yellow colors.  The  highest  protein  content  comparing  to  the control  cultivar  ‘Zolushka’  was  detected  in  ‘Marusya’ 23.60%  in  2014,  20.94%  in  2015;  and  ‘Zoloto  Sibiry’ 19.79%  in  2016.  The  observed  results  confirmed  that contents  change of  proteins,  sucrose, and  even micro and macroelements depended on the climatic conditions. In the hot and dry summer the protein content, depending on cultivar increased 18.31% to 23.60%, in 2014, and 17.81 to 20.94% in 2015. The same occurred  with zinc 19.63  to  28.68  mg/kg  in  2014,  and  20.14  to  27.54  to 2015;  and  iron  2.0  to  3.2  mg/kg  in  2014  and  1.6-1.9 mg/kg in 2015.